A Mujerista Liberation Psychology Perspective on Testimonio to Cultivate Decolonial Healing. Issue 2 (3rd July 2022) - Fernández, Jesica Siham
Abstract: Grounded in a liberation psychology mujerista epistemology and a decolonial feminist standpoint, the article describes the development and application of testimonio as a resource toward healing. The application of this resource goes beyond the classroom to include clinical settings. By bridging Latin America liberation psychology within LatCrit theory, the article describes testimonio as a decolonial feminist mujerista strategy to cultivate decolonial healing through storytelling. Healing is conceptualized as a process of reconstituting the self, individually, relationally, and collectively, through life stories. Extending this definition, decolonial healing is experiencing community well-being through relational critically reflexive dialogues that facilitate a critical social analysis, mutual reciprocal recognitions, and radical hope. Building on evidence that identifies testimonio as a pedagogical and methodological tool, this article purports that the sociopolitical process of testimoniar can serve as a therapeutic mujerista strategy to support community well-being. The sociopolitical elements of testimonio toward decolonial healing experiences, as a potential therapeutic resource, are discussed through a thematic analysis of Latinx students' reflections featured in their Testimoniando El Presente essay assignment. Testimonios were conducted with their mothers, friends, siblings, or mentors and written within in the context of an online undergraduate course. Through an analysis of Latinx students' written reflections, evidence in support of mujerista strategies like testimonio that can complement existing decolonial practices and healing therapies are discussed. The conclusion offers an invitation to engage a mujerista epistemology, specifically adapting testimonio as a resource to support decolonial healing among Latinx students living in precarious times.